2020
DOI: 10.5114/jcb.2020.96871
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of initial computed tomography-based target delineation and subsequent magnetic resonance imaging-based target delineation for cervical cancer brachytherapy

Abstract: Purpose: For cervical brachytherapy planning, magnetic resonance imaging (MRI) is preferable to computed tomography (CT) for target delineation. However, due to logistical and financial restrictions, in-room MRI is sometimes not routinely available in brachytherapy centers. Our institution has created a workflow that integrates MRI-based target delineation with an in-room CT scanner, with the aim of improving target coverage and conformality. This study reports the initial dosimetric results with using this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This approach could incorporate MRI-based target definition while retaining the advantages of a CT-based workflow. Dose analysis [61] showed that MRI fusion allowed the dose distribution to be adjusted according to individual anatomical characteristics, thus reducing excessive or insufficient coverage. Another study conducted by Choong et al [55] obtained both MRI and CT with applicators in situ at F1, and subsequently registered these images in the follow-up fraction CT images, yielding promising results.…”
Section: Ct/mri-guided Bt: Prominent Combinationmentioning
confidence: 99%
“…This approach could incorporate MRI-based target definition while retaining the advantages of a CT-based workflow. Dose analysis [61] showed that MRI fusion allowed the dose distribution to be adjusted according to individual anatomical characteristics, thus reducing excessive or insufficient coverage. Another study conducted by Choong et al [55] obtained both MRI and CT with applicators in situ at F1, and subsequently registered these images in the follow-up fraction CT images, yielding promising results.…”
Section: Ct/mri-guided Bt: Prominent Combinationmentioning
confidence: 99%
“…Nowadays, image-guided adaptive brachytherapy (IGABT) has gained considerable attention, as it can improve the therapeutic efficacy of tumor control without enhancing the obvious toxicity of organs at risk (OARs). [1][2][3][4][5] However, the local control rate in LACC can fall off for the unfavorable isodose of the high-risk clinical target volume (HR CTV) treated with ICBT only in the presence of characteristics such as large tumor volume, eccentric location, irregular shape, and parametrial or other site invasions. 6 Based on previous studies, imageguided adaptive intracavitary/interstitial brachytherapy (IC/IS IGABT) is superior in terms of dosimetry advantages and local control rate for the treatment of large tumors.…”
Section: Introductionmentioning
confidence: 99%
“…External beam radiotherapy (EBRT) combined with synchronous chemotherapy followed by intracavitary brachytherapy (ICBT) is the traditional standard strategy for locally advanced cervical cancer (LACC). Nowadays, image‐guided adaptive brachytherapy (IGABT) has gained considerable attention, as it can improve the therapeutic efficacy of tumor control without enhancing the obvious toxicity of organs at risk (OARs) 1–5 . However, the local control rate in LACC can fall off for the unfavorable isodose of the high‐risk clinical target volume (HR CTV) treated with ICBT only in the presence of characteristics such as large tumor volume, eccentric location, irregular shape, and parametrial or other site invasions 6 .…”
Section: Introductionmentioning
confidence: 99%